Perilaku Masyarakat dalam Menunaikan Zakat Pertanian di Jorong Bawah Duku, Kabupaten Solok - Cici Sartika (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Community behavior in paying agricultural zakat in Jorong Bawah Duku Nagari Koto Baru, Kubung District, Solok Regency. The purpose of this discussion is to find out how the behavior of the community in paying agricultural zakat in Jorong Bawah Duku Nagari Koto Baru. The research method that the author uses is (field research) field research with a qualitative descriptive approach. The data collection techniques that the author uses are field observations, in-depth interviews with the people of Jorong Bawah Duku and documentation. Data collection techniques with interviews, documentation studies. The data analysis technique was carried out since doing data reduction, displaying data and drawing research conclusions. The results of the study that the authors found that the behavior of muzakki in paying agricultural zakat was carried out by means of their own calculations, namely by using the agricultural zakat calculation method 71.4% and 28.6% by using calculations that did not follow sharia rules, namely in accordance with sincerity. Most of the muzakki pay zakat according to haul 92.9% and those who pay during Ramadan 7.1%. While the place to pay zakat, most of the muzakki pay directly to mustahiq 92.9%, namely mosques, neighbors or underprivileged families and 7.1% pay through the BAZNAS institution. And the form of agricultural zakat distributed by muzakki is in two forms, namely in the form of cash and rice. 71.4% of respondents paid in cash and 28.6% paid zakat in the form of rice or paddy.